KARAKTERISTIK PERTUMBUHAN FISIOLOGIS DAN ANATOMI TANAMAN KEDELAI (GLYCINE MAX L.) TERHADAP TINGKAT KONSENTRASI AB MIX PADA SISTEM HIDROPONIK - Hidayatullah, Careca Sepdihan Rahmat (Politeknik Pembangunan Pertanian Medan, 2025)
Soybean plants (Glycine max L.) are among the primary sources of vegetable oil and require essential nutrients to support their growth and yield. In order to enhance the morphological quality and seed production of soybean such as plant height, stem diameter, number of filled pods, and number of seeds per plant alternative developments in hydroponic technology are needed. This study aimed to evaluate the effects of different concentrations of AB Mix nutrient solution on the growth, physiological, and anatomical characteristics of soybean plants in a hydroponic system. The experiment was conducted in a greenhouse at the Lower Cikabayan Garden, Bogor Agricultural University, Indonesia, using a simple Randomized Complete Block Design (RCBD). The treatments consisted of three AB Mix concentration levels: 1/2x, 1x, and 2x the standard concentration. The 1x AB Mix concentration treatment (10 mL L⁻¹) consistently resulted in relatively higher plant height and number of leaves—by 7.9% and 0.9%, respectively—compared to the 1/2x and 2x treatments. However, the differences were not statistically significant. The study concluded that varying AB Mix concentrations (1/2x, 1x, and 2x) did not significantly affect the growth, physiology, or anatomy of soybean plants in a hydroponic system. Further research is recommended to explore the interaction between AB Mix concentrations and various soybean genotypes to achieve optimal production